2022
DOI: 10.1097/won.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

Projected Augmented Reality (P-AR) for Enhancing Nursing Education About Pressure Injury

Abstract: PURPOSE: To describe results of a study evaluating a Projected Augmented Reality (P-AR) system for its potential to enhance nursing education about pressure injuries. DESIGN: Pilot evaluation survey. SUBJECTS AND SETTING: The sample comprised nursing students and faculty at a school of nursing in a large, Midwestern public university. A total of 32 participants, which included 27 students (30% BSN, 44% MN, and 26% DNP students; 81% female) and 5 faculty members (80% female) participated. METHODS: The P-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It focused on matters such as scaling and distributing learning and increasing efficiencies through online activities and assessments 107,108 . Other foci included augmentation of current teaching methods, primarily through the use of additional learning and feedback opportunities, and the use of technology to allow students to visualise more than they would with traditional teaching methods 109–111 . We were however encouraged by a more recent work redefining education through technology 104–106 …”
Section: Technology‐led Transformations In Hpe: Literature Exploratio...mentioning
confidence: 99%
“…It focused on matters such as scaling and distributing learning and increasing efficiencies through online activities and assessments 107,108 . Other foci included augmentation of current teaching methods, primarily through the use of additional learning and feedback opportunities, and the use of technology to allow students to visualise more than they would with traditional teaching methods 109–111 . We were however encouraged by a more recent work redefining education through technology 104–106 …”
Section: Technology‐led Transformations In Hpe: Literature Exploratio...mentioning
confidence: 99%
“…Maybe. Nurse educators are currently conducting research studies to examine the effects of AR on student learning (Bliss et al, 2022; Kim et al, 2021; Menon et al, 2022). Though the researchers used small samples, these pilot studies have shown that AR can enhance students’ cognitive and psychomotor performance.…”
mentioning
confidence: 99%